The Effect Assessment of Industrial Activities on Air Pollution at Cimerwa and its Surrounding Areas, Rusizi-District-Rwanda - Elisephane, Irankunda; Ishigaki, Yo (International Journal of Sustainable Energy and Environmental Research, 2020)
In the last three decades, considerable efforts to protect people from ambient air pollutants exposure have been made. However, vulnerable populations groups, including the elderly, children, and pregnant women, and other people present with respiratory problems are most concern as their immune system is weak. The main aim of this paper was to assess the effect of industrial activities on air pollution at CIMERWA Cement factory, one of the biggest industries in Rwanda and its surrounding areas. Portable air quality sensors (Pockets PM2.5 Sensors) were used for monitoring the concentration levels of PM2.5 and PM10. Questionnaire method was also used for investigating the presence and potential sources of pollution across the site. Survey results indicated that dust; noise pollution and Particulate Matter come up as the main pollutants in the areas where industrial activities and vehicle emissions are the potential sources. Sampling activities showed that the average concentration levels of PM2.5 are in range of 28.0–32.0µg/m3 during morning hours and 46.0-50.0µg/m3 during evening hours while that of PM10 are in range of 51.0-55.0µg/m3 and 69.0-73.0µg/m3 during morning and evening hours respectively. Results showed that air pollutants were present around the considered area that is why the appropriate mitigation and management strategies concerning these pollutants were highly recommended as the contribution of this paper.